2022
DOI: 10.5312/wjo.v13.i11.1029
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported dissatisfaction following second side in staged bilateral total knee arthroplasty: A systematic review

Abstract: BACKGROUND Around one third of patients who undergo total knee arthroplasty (TKA) will eventually have the contralateral knee replaced. Overall patient satisfaction after staged bilateral total knee arthroplasty procedures performed on different days is reportedly similar to unilateral TKA. Nevertheless, in our anecdotal experience patients often report less satisfying outcomes following the second side. A cursory review of available literature tended to confirm that observation. We sought therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…This seems to be particularly key in TKA. Multiple reviews have shown that the second TKA has significantly worse PROMs than the first[ 40 , 41 ] even in patients who were satisfied overall, and in patients who reported dissatisfaction with one of their TKAs, there was 50% greater risk of dissatisfaction at 1 year with the second TKA. However, from an objective surgical course and recovery perspective, our study demonstrates that operative time for THA, LOS, and postoperative discharge disposition can be anticipated for patients undergoing the second side TJA.…”
Section: Discussionmentioning
confidence: 99%
“…This seems to be particularly key in TKA. Multiple reviews have shown that the second TKA has significantly worse PROMs than the first[ 40 , 41 ] even in patients who were satisfied overall, and in patients who reported dissatisfaction with one of their TKAs, there was 50% greater risk of dissatisfaction at 1 year with the second TKA. However, from an objective surgical course and recovery perspective, our study demonstrates that operative time for THA, LOS, and postoperative discharge disposition can be anticipated for patients undergoing the second side TJA.…”
Section: Discussionmentioning
confidence: 99%